Addressing Corruption in Military Institutions. (12th September 2017) - Pyman, Mark
Abstract : Military training places great emphasis on values such as integrity, and the armed forces usually hold a position of trust at the heart of the nation. However, abuses such as corruption in procurement, nepotism in officer promotion, abuse of position by general officers, infiltration by sectarian groups and use of military intelligence to smear adversaries show that the reality can be very different. In the last decade the issue has become more visible to militaries and policymakers; from scandals, social media exposure, and the wars in Iraq and Afghanistan. Corruption has also emerged as an international security issue. Military forces and Defense Ministries in many developing countries seek to limit corruption in their institutions. Incomprehension about corruption by international security assistance forces also inadvertently makes the situation worse. Based on extensive research, this paper reviews the nature of corruption in defense, describes corruption reform experiences in a range of different countries and describes how to set about such reforms. It describes several innovative approaches currently being explored by the military, international policy-makers and civil society, including approaches that quantitatively compare the corruption vulnerabilities of national militaries, and new ways to train military leadership in combatting corruption.